Incumbent Failure in the 2018 Riau Governor Election Contest - Auradian Marta; Utang Suwaryo; Affan Sulaeman; Leo Agustino (Jurnal Public Policy, 2022)
This study aimsto explain the factors that led to the defeat of incumbent candidate ArsyadjuliandiRachman-Suyatno in the election of the Governor of Riau in 2018. This empirical fact is interesting to analyze because the incumbent pair is supported by the majority of seats in parliament and Riau is the base area of the Golkar Party. This study uses qualitative research methods using data collection techniques through interviews and document sources such as books, research journals, survey results, and articles in mass media and online media. The results of this study indicate that 4 factors led to the defeat of the incumbent pair in the election of the Governor of Riau in 2018 namely (1) Government performance that is not well socialized; (2) Machinery of political parties that have not worked optimally and effectively; (3) Effect of the ulama; and (4) Political branding of incumbent candidate pairs who are unsuccessful. The conclusion in this study is that candidate figures are important indirect regional head elections, but also a political marketing strategy is needed by carrying out political branding so that the message to be conveyed to voters towards candidate figures is acceptable so that they are ultimately chosen by the voters.